Sense of Ethnic Belonging: Relation With Well-Being and Psychological Distress in Inhabitants of the Mapuche Conflict Area, Chile - García, Felipe E.; Villagrán, Loreto; Ahumada, María Constanza; Inzunza, Nadia; Schuffeneger, Katherine; Garabito, Sandra (Frontiers in Psychology, 2021)
Research has shown that discrimination experienced by a group causes harm to the health and well-being of its members. With regard to the identity of the members of a group, maintaining a positive evaluation of the group may involve the activation of mechanisms that devalue the out-group as a way of raising the endo-group, causing discrimination towards the out-group. In the Chilean context, one group that has historically suffered discrimination and rights violations is the Mapuche people. The aim of this study was to evaluate Collective Identity, Socially Politicised Identity, perception of experiences of discrimination, psychological well-being and uneasiness in inhabitants of the Mapuche conflict zone according to their sense of belonging to their ethnic group (Mapuche, Mestizo, Caucasian) and the relationship between them. It is a descriptive, correlative and cross-sectional design. The participants correspond to 200 people, 94 men (47%), 106 women (53%), between 18 and 83 years old (M = 39.02; SD = 13.45), who have been living for at least one year in communities in the Araucanía Region. The sample was stratified by 30% of participants with a sense of Mapuche ethnicity, 33.5% Caucasian and 36.5% mestizo. The results show that participants with a sense of Mapuche ethnicity have more experiences of discrimination, collective identity and support for the Mapuche social movement and its methods. Well-being is directly related to collective identity. A regression analysis was done for emotional distress and psychological well-being. The interaction between experiences of discrimination and collective identity has a significant influence. Collective identity and experiences of discrimination in themselves, as well as the interaction between them, predict psychological well-being. The results suggest that the importance of the Mapuche group's identity phenomena is related to a broad socio-historical context that leads them to identify themselves as a collective in conditions of inequality. The relationship between well-being and collective identity would be explained through the sense of ethnic belonging as a factor in protecting mental health.